The chief witness escape from China's modern-day concentration camps - Sauytbay, Sayragul 1977-; Cavelius, Alexandra 1967- (Scribe Publications, 2021)
In recent years, China's north-western province has become home to over 1,200 penal camps - modern-day gulags that are estimated to house three million members of the Kazakh and Uyghur minorities. Imprisoned solely due to their ethnicity. While incarcerated, Sayragul Sauytbay gained access to secret information that revealed Beijing's long-term plans to undermine not only its minorities, but democracies around the world. This rare testimony from the biggest surveillance state in the world reveals the full, frightening scope of China's tyrannical ambitions
Keywords: Zhong guo gong chan dang; Uiguren; Politische Verfolgung; Sinkiang; Sauytbay, Sayragul; Kazakhs / China / Social conditions / 20th century; Ethnic conflict / China / Xinjiang Uygur Zizhiqu; China / Politics and government / 21st century; Ethnic conflict; Politics and government; China; China / Xinjiang Uygur Zizhiqu; 1900-2099; Erlebnisbericht